The Importance of Intangible Assets in Achieving a Company's Competitive Advantage - Safitri, Dina (International Journal of Economics, Business, and Entrepreneurship, 2024)
This paper aims to investigate the role of intangible assets in providing a competitive advantage for organizations. To achieve this aim, a meta-analysis of journal articles sourced from EBSCOhost, JSTOR, Emerald Insight, Science Direct, and Wiley Online Library was conducted. Articles were selected based on their use of the English language and publication dates ranging from 2012 to 2024. However, relevant articles published prior to 2012 were also included in the analysis. The study found a positive relationship across all four categories of intangible assets. Intellectual capital, particularly in the forms of human capital and human assets, emerged as the most critical factor in providing a competitive edge. This includes employee education levels, experience, skill development, and knowledge.